Chemical cues involved in the host foraging behavior of Psyttalia concolor wasps to locate the olive fruit fly Bactrocera oleae - Bogka, Giannoula; Anastasaki, Eirini; Milonas, Panagiotis G.; Psoma, Aikaterini; Kabourakis, Emmanouil M.; Zwaan, Bas J.; Pannebakker, Bart A.; Fatouros, Nina E. (Frontiers in Ecology and Evolution, 2023)
Foraging parasitoids rely on infochemicals, derived from the habitat, host plant and/or host insect itself. Here, we studied the olive fruit fly Bactrocera oleae (Rossi) (Diptera: Tephritidae), a major pest in olive agroecosystem and its larval parasitoid, Psyttalia concolor (Szépligeti) (Hymenoptera: Braconidae), a well-established and abundant wasp in Crete. To improve parasitoid’s efficiency as biological control agent, more knowledge on its host location behavior is required. The aim of this study was to investigate the role of oviposition- (OIPVs) and herbivore-induced plant volatiles (HIPVs) emitted by olive trees upon infestation by B. oleae as well as cues emitted by B. oleae, e.g., pheromones, therein. We conducted two-choice bioassays to test the preference of P. concolor to different olfactory stimuli. Moreover, we collected headspace volatiles from olive fruits and branches to investigate whether egg or larval infestation changes volatile emissions locally or/and systemically. We found that P. concolor wasps showed a strong preference to volatiles of B. oleae larval-infested fruits (HIPVs) compared to clean air, non-infested, egg-infested, and mechanical-damaged fruits. But they were not able to discriminate between volatiles of non-infested and larval-infested branches. In addition, the wasps were attracted to cues emitted from the virgin B. oleae females. They were neither attracted to those cues emitted by the virgin males, mated males and females nor to the olive fruits with or without the cues of the oviposition marking of the B. oleae. We found important qualitative differences in volatile profiles of egg- and larval-infested fruits: 19 volatile compounds were only detected in infested fruits, such as the terpenoids (E)-β-ocimene and (E,E)-α-farnesene. Moreover, volatile analysis showed that olives change volatile emissions locally and systemically in response to larval infestation. Our results suggest that both HIPVs and host cues play an important role to P. concolor during host location. Further knowledge on the chemical compounds utilized by the parasitoid to locate infested fruits could help application in olive orchards and improve olive fruit fly control by natural enemies.